Oxidation Behavior of Quaternary Co-20Re-25Cr-3Si Alloy at Laboratory Air - Liu, Mingfeng; Xiang, Junhuai; Wei, Hua; Pan, Xiuhong; Xu, Xunhu; Wang, Ling; Zhang, Shuai (Frontiers in Materials, 2021)
The iso-thermal oxidation of the quaternary Co-20Re-25Cr-3Si alloy at 1,000–1,200 C under laboratory air for 24 h has been studied. The oxidation kinetics at 1,000–1,200 C follow parabolic law perfectly and the value of oxidation activation energy is 220.74 kJ/mol. Unlike the experimental condition of 0.1 MPa pure oxygen, under laboratory air Co-20Re-25Cr-3Si alloy presents a good oxidation resistance due to the formation of a dense and continuous layer of Cr2O3 in contact with the alloy. A 79% drop in oxygen pressure has changed the oxidation mode from catastrophic oxidation to mild oxidation. The thickness of the protective Cr2O3 layer decreases when temperature increases. Therefore, Co-20Re-25Cr-3Si alloy shows the best oxidation resistance at 1,000 C. Moreover, from another perspective, compared with Co-17Re-23Cr-3Si alloy, the addition of about 2% Cr can also improve the oxidation resistance of the alloy greatly by forming the protective Cr2O3 layer.